Diagonal crack width towards the experimental results - Ostromęcki, Rafał (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The results of research on diagonal crack width in a single span RC beams were presented in the article. Eurocode 2 rules do not require the direct control of shear crack width. It is assumed, that reinforcement designed to carry the transverse force is also enough to limit the crack width. Experiments were led on beams grouped into four series differing in the links spacing and area of longitudinal tensile reinforcement anchored on supports. The transverse reinforcement steel was of fyd =500MPa The crack width was measured in the following phases of loading. The force was estimated for every series, which was represented by the load level for which the serviceability limit state should be controlled. Maximum crack width was read for this value of force and compared to the limit of 0,3mm. The conclusion was drawn, that crack width is not a critical factor for beams designed for shear with the use of Eurocode and Polish National Annex.